2004
DOI: 10.1182/blood-2003-05-1605
|View full text |Cite
|
Sign up to set email alerts
|

A novel mechanism for imatinib mesylate–induced cell death of BCR-ABL–positive human leukemic cells: caspase-independent, necrosis-like programmed cell death mediated by serine protease activity

Abstract: Caspase-independent programmed cell death can exhibit either an apoptosis-like or a necrosis-like morphology. The ABL kinase inhibitor, imatinib mesylate, has been reported to induce apoptosis of BCR-ABL-positive cells in a caspasedependent fashion. We investigated whether caspases alone were the mediators of imatinib mesylate-induced cell death. In contrast to previous reports, we found that a broad caspase inhibitor, zVAD-fmk, failed to prevent the death of imatinib mesylate-treated BCR-ABL-positive human le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
75
2
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(81 citation statements)
references
References 63 publications
3
75
2
1
Order By: Relevance
“…This finding is also reinforced by the observation of a diminished cell rate proliferation in K562 clones, nevertheless resistant in term of apoptosis to Bcr-Abl inhibitors. The caspaseindependent counterpart of the imatinib-induced cell death could be likely owing to activation of HtrA serine peptidase 2 (HTRA2) as described recently (Okada et al, 2004) or to other currently unrevealed mechanisms. However, in our hands, neither tosyl-L-lysine chloromethylketone, a general trypsin-like inhibitor, nor the more specific OMI/HTRA2 inhibitor, UFC101, were able to further increase cell metabolism in the presence of Bcr-Abl inhibitors.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…This finding is also reinforced by the observation of a diminished cell rate proliferation in K562 clones, nevertheless resistant in term of apoptosis to Bcr-Abl inhibitors. The caspaseindependent counterpart of the imatinib-induced cell death could be likely owing to activation of HtrA serine peptidase 2 (HTRA2) as described recently (Okada et al, 2004) or to other currently unrevealed mechanisms. However, in our hands, neither tosyl-L-lysine chloromethylketone, a general trypsin-like inhibitor, nor the more specific OMI/HTRA2 inhibitor, UFC101, were able to further increase cell metabolism in the presence of Bcr-Abl inhibitors.…”
Section: Discussionmentioning
confidence: 95%
“…Finally, imatinib-induced caspase activation and differentiation were unaffected by antioxidants, suggesting that reactive oxygen species production is not involved in these processes (not shown). A recent study by Okada et al (2004) reported that imatinib-induced cell death in CML cells occurs by both caspase-dependent and -independent mechanisms. The partial caspase independence of Bcr-Abl inhibitors is confirmed in our study by the observation that even in the presence of ZVAD-fmk, a significant loss of cell metabolism (around 50%) could be still detected upon imatinib and PD166326 treatment of CML cell lines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is in accordance with a recent study conducted on K-562, a BCR-ABL-positive cell line, exposed to IM. The authors demonstrated that IM induced a caspase-independent, necrosis-like cell death mediated by the serine protease activity of Omi/HtrA2 (Okada et al, 2004). Other studies demonstrated an inhibitory effect of IM on PDGF-R-expressing cell lines, suggesting that this effect was mediated mainly through promoting growth arrest rather than apoptosis (Kilic et al, 2000).…”
Section: Discussionmentioning
confidence: 97%
“…Specifically, TLCK and TPCK have been shown to block activation of NFκB [35], prevent the activation of pp70(s6k), a mitogenrelated kinase [36], and to suppress the processing of caspases in some model systems [37,38]. In contrast, these two proteases have been shown to both induce and enhance cell death upon treatment with various cytotoxic agents [39][40][41].…”
Section: Caspase Independent Dna Degradationmentioning
confidence: 99%